Structural constraints on pronoun binding and coreference: evidence from eye movements during reading - Cunnings, Ian; Patterson, Clare; Felser, Claudia (Frontiers in Psychology, 2015)
A number of recent studies have investigated how syntactic and non-syntactic constraints combine to cue memory retrieval during anaphora resolution. In this paper we investigate how syntactic constraints and gender congruence interact to guide memory retrieval during the resolution of subject pronouns. Subject pronouns are always technically ambiguous, and the application of syntactic constraints on their interpretation depends on properties of the antecedent that is to be retrieved. While pronouns can freely corefer with non-quantified referential antecedents, linking a pronoun to a quantified antecedent is only possible in certain syntactic configurations via variable binding. We report the results from a judgement task and three online reading comprehension experiments investigating pronoun resolution with quantified and non-quantified antecedents. Results from both the judgement task and participants’ eye movements during reading indicate that comprehenders freely allow pronouns to corefer with non-quantified antecedents, but that retrieval of quantified antecedents is restricted to specific syntactic environments. We interpret our findings as indicating that syntactic constraints constitute highly weighted cues to memory retrieval during anaphora resolution.